2015
DOI: 10.1097/md.0000000000001105
|View full text |Cite|
|
Sign up to set email alerts
|

Perirenal Fat and Association With Metabolic Risk Factors

Abstract: Incidence of esophageal adenocarcinoma (EAC) has risen rapidly over the past decades in Western countries. As a premalignant lesion, Barrett's esophagus (BE) is an established risk factor of EAC. This study estimated the impact of surveillance endoscopy for BE on population's survival upon EAC by a whole-population cost-effectiveness analysis among modeled Western population.Possibilities and survival payoffs were retrieved through literature searching based on PubMed database. Patients with BE were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 61 publications
1
45
0
1
Order By: Relevance
“…In recent studies, PUFT has demonstrated a close association with several cardiovascular and metabolic risk factors such as fasting plasma glucose, uric acid, HDL‐C, or tryglicerides, and our data seem to confirm these results (see Table ). Moreover, PUFT has been shown to correlate with visceral fat and with total adiposity better than anthropometric parameters of obesity, so the relationship between PUFT and eGFR could be more accurate and less affected by the abovementioned bias.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In recent studies, PUFT has demonstrated a close association with several cardiovascular and metabolic risk factors such as fasting plasma glucose, uric acid, HDL‐C, or tryglicerides, and our data seem to confirm these results (see Table ). Moreover, PUFT has been shown to correlate with visceral fat and with total adiposity better than anthropometric parameters of obesity, so the relationship between PUFT and eGFR could be more accurate and less affected by the abovementioned bias.…”
Section: Discussionsupporting
confidence: 89%
“…Like BMI or WC, PUFT has shown a close relationship with microalbuminuria and reduced glomerular filtration rate in animal models . A few studies on diabetic or obese patients would seem to confirm this finding even in humans . No data are available about nondiabetic patients or in hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of MetS and risk factors for atherosclerosis may be associated with an increase in the accumulation of visceral and perirenal fat deposits in this population [26][27][28]. In a recent study in Ecuador, the prevalence of MetS was 66.0% in women and 47.1% in men.…”
Section: Research Articlementioning
confidence: 99%
“…The MetS and risk factors for atherosclerosis may be associated with an increase in the accumulation of visceral and perirenal fat deposits in this population [26][27][28]. The high prevalence of MetS and risk factors for atherosclerosis may be associated with an increase in the accumulation of visceral and perirenal fat deposits in this population [26][27][28].…”
Section: Research Articlementioning
confidence: 99%
“…Obesity is associated with a large number of diseases such as hypertension, diabetes, heart disease, brain disease, sleep disorders, cancer, infertility, pain, skin infections, metabolic syndrome (MetS), gastric ulcers and gallstones [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%